Bioequivalence study of BETALOC-XR™ (Drug International Ltd, Bangladesh) and METOPROLOL 100 STADA™ (STADA Pharm Gmbh, Germany) as open-label, two-way crossover and randomized fashion among healthy male volunteers - Kumar Sarker, Uttam; Farhana, Fatiha; Islam, Atikul; Misbahuddin, Mir; Mollah, Md. Elias; Roy, Balaram; Islam, Md. Rabiul (Asian Journal of Pharmaceutical Research and Development, 2022)
Bioequivalence study of two oral formulations of metoprolol 100 mg tablet was brought about in 16 healthy male Bangladeshi normal individuals as crossover-randomized fashion. The test and reference formulated products were BETALOC-XR™ (Drug International Ltd, Bangladesh) and METOPROLOL 100 STADA™ (STADA Pharm Gmbh, Germany). Each tablet was delivered with 150 mL of water to every normal individual after whole night fasting on two treatment days separated by more than one week washout period. After administering drug, blood samples were collected serially for a period of 24 hours. A validated HPLC method was used to estimate the plasma concentrations of metoprolol. The pharmacokinetic parameters Cmax, Tmax, AUC0→24h, t1/2, and Kel were determined in this study. The mean (± SD) AUC0→24h for test drug BETALOC-XRTM was 490.3 ± 187.5 ng/hr/mL whereas for reference drug METOPROLOL 100 STADATM it was 559.9 ± 267.2 ng/hr/mL. The relative bioavailability (BETALOC-XRTM/METOPROLOL 100 STADATM ratio) was 87.5%. The Cmax, tmax, half-life of elimination (t1/2) and the rate of elimination (Kel) for test drug was 170.9 ± 78.3 ng/mL, 2.3 ± 0.8 hours, 1.2 ± 2.0 hour and 0.4362 whereas for reference drug was 209.1 ± 91.3 ng/mL, 1.7 ± 0.7 hours, 1.3 ± 2.2 hour and 0.5875 respectively. Based on these statistical hypothesis it was conjecture that a BETALOC-XRTM tablet is bioequivalent to a METOPROLOL 100 STADATM tablet.